Digital Customer Engagement: A Systematic Review of Key Predictors Across Digital Platforms - Andhi Febisatria (CV. KAMPUS AKADEMIK PUBLISING, 2026)
. The rapid advancement of digital technologies has intensified academic attention toward Digital Customer Engagement (DCE) as a strategic construct in digital marketing. This study aims to identify and synthesize the key determinants of DCE and to map variations in its predictors across different digital platforms using a Systematic Literature Review approach. The synthesis reveals that DCE represents a complex and multidimensional construct shaped by the interaction of technological factors, digital marketing strategies, user experience design, and customer psychological mechanisms. Empirical evidence confirms that platform quality, digital engagement activities, and customer experience design significantly influence customer engagement. Trust, emotions, and perceived value function as reinforcing mechanisms that mediate the relationship between digital stimuli and engagement responses. Clear differences in DCE predictors emerge across digital platforms, with social media and live-streaming emphasizing interactivity and real-time experience, while e-commerce and transactional digital services are more strongly influenced by ease of use, experience consistency, and digital service quality. In digital B2B contexts, relational approaches and activity-based engagement dominate as the primary determinants of customer engagement. These findings contribute theoretically by integrating DCE predictors across digital contexts and provide practical implications for developing more contextual and engagement-oriented digital marketing strategies.